American prisons: their past, present and future - Musick, David (Routledge, Taylor & Francis Group, 2017)
Introduction -- A brief history of imprisonment in America (1600-1900) -- The twentieth century prison building binge -- Federal prisons in the twentieth and twenty-first centuries -- Profiting from punishment: corporations and American prisons -- The final solution - capital punishment -- Less visible prison minorities - women, children and the elderly -- Prison by-products - violence and disease -- The future of prisons in the United States